The Democricy to Come. Issue 1 (July 2017) - Bennington, Geoffrey
Abstract : A recurrent typographical slip makes a democrat of Democritus, Demokratos of Demokritos, in an exemplary instance of the atomists' persistent analogy of atoms and letters. This essay argues that the rhythmic resonances between ancient materialism and democracy can be read in terms of a fundamental scatter that tends to deconstruct the teleologism endemic in the philosophical tradition's thinking about politics (and indeed matter). The curious resistance that scatter opposes to any kind of telos (including that of any absolute scatter) might itself make deconstruction interestingly resonate with the differential vibrations of string theory.